HUBUNGAN MEROKOK DAN KONSUMSI ALKOHOL DENGAN KEJADIAN PENYAKIT HIPERTENSI PADA MASYARAKAT WILAYAH PESISIR - Muhammad Syahrir; Yusuf Sabilu; Wa Ode Salma (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
One of the non-communicable diseases that attack the community today is hypertension or high blood pressure. Hypertension is still a public health problem, including those in coastal areas. The prevalence of hypertension in coastal areas is higher than in mountainous areas. The purpose of this study was to analyze the factors associated with the incidence of hypertension in the coastal community of Kec. East Kolono Kab. South Konawe. Methods: The design of this study used a Cross Sectional Study approach. The sampling technique used is Probability Sampling, namely Simple Random Sampling, with a sample size of 197 respondents. The instruments used are Questionnaires and Spignomanometer to measure blood pressure. Data were analyzed using Chi Square test with a significance value of P Value < 0.05. Research Results: There is no relationship between smoking and the incidence of hypertension in the community with a significance test value of P Value = 0.611. There is no relationship between alcohol consumption and the incidence of hypertension in coastal communities with a significance test value of P Value = 0.555. Smoking activity and alcohol consumption are not associated with the incidence of hypertension in coastal communities. health workers intensify the implementation of communication, education and providing information to the public about the dangers of hypertension.